2011
DOI: 10.1103/physrevb.83.174116
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale hydride formation at dislocations in palladium:Ab initiotheory and inelastic neutron scattering measurements

Abstract: Hydrogen arranges at dislocations in palladium to form nanoscale hydrides, changing the vibrational spectra. An ab initio hydrogen potential energy model versus Pd neighbor distances allows us to predict the vibrational excitations for H from absolute zero up to room temperature adjacent to a partial dislocation and with strain. Using the equilibrium distribution of hydrogen with temperature, we predict excitation spectra to explain new incoherent inelastic neutron-scattering measurements. At 0K, dislocation c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(46 reference statements)
2
4
0
Order By: Relevance
“…Extrapolation of the Ann-1/Ann-2 Arrhenius response to higher temperature demonstrates the 350-and 400-K measurements of the Def-1 sample are dominated by bulk hydrogen diffusion, not hydrogen DPD. Hydrogen de-trapping above T ∼ 300 K leads to bulk diffusion behavior in deformed Pd, consistent with the elasticity model for hydrogen occupation of dislocation traps in Pd [20]. We therefore include the two highest T measurements of Def-1 in the fit of the bulk hydrogen diffusion Arrhenius.…”
supporting
confidence: 58%
See 3 more Smart Citations
“…Extrapolation of the Ann-1/Ann-2 Arrhenius response to higher temperature demonstrates the 350-and 400-K measurements of the Def-1 sample are dominated by bulk hydrogen diffusion, not hydrogen DPD. Hydrogen de-trapping above T ∼ 300 K leads to bulk diffusion behavior in deformed Pd, consistent with the elasticity model for hydrogen occupation of dislocation traps in Pd [20]. We therefore include the two highest T measurements of Def-1 in the fit of the bulk hydrogen diffusion Arrhenius.…”
supporting
confidence: 58%
“…The time-of-flight neutron backscattering silicon spectrometer (BASIS) at the Spallation Neutron Source at Oak Ridge National Laboratory [18] and the High-Flux Backscattering Spectrometer (HFBS) at the National Institute of Standards and Technology Center for Neutron Research [19] were used to quantify trapped hydrogen kinetics with QENS. The sample material for the BASIS and HFBS experiments was 0.25-mm-thick 99.98% pure (metals basis) cold-rolled polycrystalline Pd sheet supplied by Alpha Aesar identical to that used previously for vibrational density of state measurements of trapped hydrogen [20][21][22]. In addition to the deformation by cold rolling, the deformed samples were cycled across the Pd-H miscibility gap (hydride cycling) to introduce additional dislocations using the procedure described in Ref.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…6 However, dislocations do not always lead to faster diffusion; one computational study used an embedded atom model potential and found reduced hydrogen diffusion along both screw and edge dislocations in Fe due to high diffusion barriers. 7 Previous studies of hydrogen near a palladium dislocation found the formation of hydrides in the dislocation core, 8 which could block pipe diffusion. Heuser et al…”
Section: Introductionmentioning
confidence: 99%